Rhamnus davurica leaf extract inhibits Fyn activation by antigen in mast cells for anti-allergic activity - Kim, Ji Hyung (BMC Complement Altern Med, 2015)
BACKGROUND: Complementary and alternative herbal medicines are recently considered as a promising approach for treating various diseases. We screened approximately 100 plant extracts for anti-allergic activity. Rhamnus davurica leaf extract showed the most potent inhibitory effect on the activation of RBL-2H3 mast cells. Although Rhamnus davurica extract has been used to treat pruritus, dysuresia, and constipation as a traditional herbal medicine in some Asian countries, an anti-allergic effect of Rhamnus davurica has not yet been demonstrated. We aimed to investigate the effect and mechanism of the leaf extract of Rhamnus davurica (LERD) on mast cells in vitro and allergic responses in vivo. METHODS: The effects of LERD on the activation of mast cells and mast cell-mediated passive cutaneous anaphylaxis (PCA) were measured in mice and two types of mast cells, mouse bone marrow-derived mast cells (BMMCs) and RBL-2H3 cells in vitro. A mechanistic study of its inhibitory effect was performed by using degranulation assay, reverse transcriptase-polymerase chain reaction, enzyme-linked immunosorbent assay, and western blotting analysis. RESULTS: LERD reversibly suppressed antigen-stimulated degranulation in BMMCs and RBL-2H3 cells, and also inhibited mRNA expression and secretion of TNF-α and IL-4 in a dose-dependent manner. In a PCA animal model, LERD significantly inhibited antigen-induced allergic response and degranulation of ear tissue mast cells. As for the mechanism of action, LERD inhibited the activation of Syk, which is the pivotal signaling protein for mast cell activation by antigen. Furthermore, LERD also impeded the activations of well-known downstream proteins such as LAT, Akt and three MAP kinases (Erk, p38 and JNK). In an in vitro kinase assay, LERD suppressed the activation of Fyn in antigen-stimulated mast cells. CONCLUSION: This study demonstrated for the first time that LERD has anti-allergic effects through inhibiting the Fyn/Syk pathway in mast cells. Therefore, this study provides scientific evidence for LERD to be used as an herbal medicine or health food for patients with allergic diseases.